SDG7 and the systematic downplaying of affordability in discourses on energy prices - Bibek Bhatta (Queen's University Belfast, Queen's Business School, 2023)
This study examines whether the current discourses and debates at international level are aligned with Sustainable Development Goal (SDG) 7 for i) affordable energy and ii) clean energy. Guided by the overarching vision of SDG7, this study assumes that both "affordably energy" and "clean energy" are of equal importance and examines their prevalence along two dimensions: parliamentary debates and news cycle. Results suggest that "clean energy" is used significantly more compared to "affordable energy" in both parliamentary debates and newspapers in the UK, US and Ireland. This is the first study that we are aware of that examines the possible incongruity between international discourses and SDG7. It also adds to the emerging debate on whether affordable energy and clean energy are of equal importance or whether one is superior to the other. It also points towards the need for a macroeconomic evaluation and cost consideration when it comes to creation of 'green jobs'. Finally, given that this incongruity is most severe in the US congress, this study also points to geopolitical implications for other countries.
Keywords: Q40; Q42; Q43; Q48; Q58; 330; SDG7; clean energy; affordable energy; green jobs; sustainable development